2012
DOI: 10.1186/1742-2094-9-276
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 secretion by microglial cells and decreased CNS expression in obesity

Abstract: BackgroundType 2 diabetes (T2D) is a strong risk factor for developing neurodegenerative pathologies. T2D patients have a deficiency in the intestinal incretin hormone GLP-1, which has been shown to exert neuroprotective and anti-inflammatory properties in the brain.MethodsHere we investigate potential sources of GLP-1 in the CNS and the effect of diabetic conditions on the proglucagon mRNA expression in the CNS. The obese mouse model ob/ob, characterized by its high levels of free fatty acids, and the microgl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 33 publications
1
56
0
3
Order By: Relevance
“…Despite the differential levels of TNFα mRNA in the BV-2 microglia treated with palmitate for 4 and 24 h, co-culturing with mHypoE-46 hypothalamic neurons resulted in a similar trend towards a decrease in TNFα mRNA in the neurons. The decrease in the mRNA of TNFα, a potent pro-inflammatory marker, in the mHypoE-46 neurons may indicate an anti-inflammatory effect of the BV-2 microglia by alternative activation, as previously suggested [20, 21]. The neuroprotective potential of microglia has also been shown in co- culture models with dopaminergic neurons [63], but the influence of microglia on palmitate-mediated neuroinflammation remains controversial.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Despite the differential levels of TNFα mRNA in the BV-2 microglia treated with palmitate for 4 and 24 h, co-culturing with mHypoE-46 hypothalamic neurons resulted in a similar trend towards a decrease in TNFα mRNA in the neurons. The decrease in the mRNA of TNFα, a potent pro-inflammatory marker, in the mHypoE-46 neurons may indicate an anti-inflammatory effect of the BV-2 microglia by alternative activation, as previously suggested [20, 21]. The neuroprotective potential of microglia has also been shown in co- culture models with dopaminergic neurons [63], but the influence of microglia on palmitate-mediated neuroinflammation remains controversial.…”
Section: Discussionmentioning
confidence: 66%
“…Previous studies have suggested that microglia are the essential players in the increased expression of inflammatory cytokines that leads to neurotoxicity in a high-fat environment [19]. On the contrary, other studies have shown that palmitate may induce an alternative, anti-inflammatory response in microglia, resulting in neuroprotection [20, 21]. It is likely that both are possible given the temporal responses necessary for resolution of an acute inflammatory response versus the chronic neuroinflammation seen with long-term exposure to high fat [22].…”
Section: Introductionmentioning
confidence: 99%
“…GLP-1 is one of two incretin peptides that are so named because their secretion by the intestines in response to food increases glucose-stimulated pancreatic insulin release [106]. Like insulin, it is produced in the brain, specifically by autonomic brainstem neurons [107] and by cerebrocortical and hippocampal microglia [108]. Also, like insulin, it has many functions outside the pancreas, including neuroprotection [109,110], promotion of neurogenesis [110,111], and potentiation of insulin signaling [112,113].…”
Section: Treating Brain Insulin Resistance In Admentioning
confidence: 99%
“…Of great interest was the finding of the proglucagon gene and the secretion of GLP-1 in a cyclic adenosine monophosphate-dependent manner in MGCs. Importantly, MGCs may be a central brain source for GLP-1 secretion, and in insulin-resistant conditions the expression and secretion of GLP-1 and mRNA expression of proglucagon are decreased, which heightens the importance of MGC activation in excess nutrition, obesity, IR, and T2DM and its relation to early neurodegeneration [63]. Accordingly, dipeptidyl peptidase 4 inhibitor therapy may have beneficial effects to attenuate the multiple toxicities that promote DC in diabetic patients.…”
Section: Therapeutic Options In DCmentioning
confidence: 99%
“…Incretin hormones such as glucagon-like peptide 1 (GLP-1) have anti-inflammatory properties, are neuroprotective, and reduce appetite in addition to stimulating insulin secretion, and are being investigated as therapies for AD [63]. GLP-1 mimetics such as extendin-4 used clinically for the treatment of T2DM are currently being used in a clinical trial by the National Institute of Aging.…”
Section: Therapeutic Options In DCmentioning
confidence: 99%